Risk factors for hospital-acquired bacteraemia – an explorative case–control study of hospital interventions. Issue 3 (4th March 2022) - Mortensen, Viggo Holten; Søgaard, Mette; Kristensen, Brian; Mygind, Lone Hagens; Schønheyder, Henrik Carl
Abstract: Background: Knowledge on hospital-related interventions as risk factors for hospital-acquired bacteraemia (HAB) is sparse. Aim: We aimed to investigate hospital interventions as risk factors for HAB. Methods: Prospectively through one year, we identified episodes of HAB in a single tertiary hospital. We used a matched incidence density sampled case–control design. Matching on sex and age group, we sampled controls (1:2) from the adult hospital population with ongoing hospitalization for ≥48 h. Using conditional logistic regression, we estimated odds ratios (OR) with 95% confidence intervals (CI). For adjusted ORs (aOR), adjustments were made for length of hospital stay, type and urgency of admission, and Charlson Comorbidity Index score level. Findings: From 15th October 2019 through 14th October 2020, we identified 115 incident episodes of HAB and matched them with 230 controls. HAB patients were more often admitted as 'medicine or emergency surgery'-patients (94% vs 87%) and had a longer hospital stay before inclusion (median days 20 vs 12). They were more frequently categorized as having a 'low level comorbidity' (58% vs 39%) but had higher prevalence of haematologic (15% vs 6%) or metastatic cancer (13% vs 10%). Our estimates for central venous catheters were aOR of 3.46 (95% CI 1.92–6.23), haemodialysis; aOR 5.05 (95% CI 1.41–18.06), immunosuppressive treatment including chemotherapy; aOR of 1.72 (95% CI 1.00–2.96). Conclusion: Central venous catheters and haemodialysis were the most prominent risk factors. Immunosuppressive treatment including therapy may play an important role in the development of HAB.